The return of her lost knight - Oliver, Melissa (Romance author) (Oliver, Melissa (Romance author). Notorious knights, 2021)
Her second chance with her lost love... To avoid a forced marriage, Lady Gwenllian plans to escape to a convent. She couldn't possibly honor another when her heart still belongs to Ralph de Kinnerton, the man she had to betray to save his life -- only to hear of his death shortly after. So how is it possible he's here at this knight's tournament? Now the pull of their unfinished past forces Gwen to question the choice she'd made for her future...